Precursor morality effect on the memristive behaviour of spin coated titania thin film / Mohd Adib Mahmudin - Mahmudin, Mohd Adib (2014)
This project is mainly about device fabrication which is titanium dioxide (TiO₂) memristor and characterized it for the electrical behaviour and physical characteristic. TiO₂ thin film is the active layer in between two different substrates which are the 60nm platinum (Pt) as the top electrode and ITO substrate as the bottom electrode in the vertical configuration. The TiO₂ thin film was deposited on the ITO substrate by sol-gel spin coating method. Prior to the deposition process, precursor molarity (Titanium (IV) isopropoxide) of the mixture of TiO₂ solution was varied to 0.05M, 0.1M, 0.2M, 0.3M, and 0.4M. After the deposition process of TiO₂ thin film, the sample was annealed for 20 minutes in the furnace with temperature of 250°C before the Pt deposited as the top electrode of the sample by using sputter coater. For the electrical characterization, current-voltge (I-V) measurement was carried out three times for each sample by considering positive voltage sweep to ensure the stable switching loop obtained. Besides, the physical characteristics of the sample that have been measured were the thickness, surface morphology, oxygen concentration and Raman measurement of the TiO2 thin film. We found that the precursor molarity does not affect the memristive behaviour however, the sample with less precursor molarity is preferred due to lesser time is required to obtain the stable switching loop.